Analisis Kelayakan Isi LKS “Pintar Pendidikan Agama Islam Berkarakter” Kelas V SD - Lisa Yulia Sari; Muhammad Aufa Muis (Jurnal Kawakib, 2021)
This study aims to identify and describe the results of the feasibility analysis of the contents of the Islamic Religious Education Smart LKS content in terms of the suitability of the material description with KI/KD, the accuracy of the material, and the content of supporting learning materials. The type of research used is library research. Literature research is research based on literature searches related to the problems to be discussed. The method used is descriptive analysis method. The primary data sources in this study were obtained from the Smart LKS for Islamic Religious Education with Character, while the secondary data were obtained from books, journals, articles, laws and regulations, and so on. All data will be collected, analyzed, interpreted as well as by interpreting the object under study. The results showed that the suitability of the description of the material with KI-KD obtained a percentage of 65%, while in terms of the accuracy of the material it obtained a percentage of 72%, and in terms of supporting learning materials it obtained a percentage of 73.2%. When viewed as a whole, the percentage of sub-components is 70%, which shows that the Smart LKS for Islamic Religious Education is worthy of being used as a companion book for learning in elementary schools